Activin promotes skin carcinogenesis by attraction and reprogramming of macrophages. Issue 1 (8th December 2016) - Antsiferova, Maria; Piwko‐Czuchra, Aleksandra; Cangkrama, Michael; Wietecha, Mateusz; Sahin, Dilara; Birkner, Katharina; Amann, Valerie C; Levesque, Mitchell; Hohl, Daniel; Dummer, Reinhard; Werner, Sabine
Abstract: Activin has emerged as an important player in different types of cancer, but the underlying mechanisms are largely unknown. We show here that activin overexpression is an early event in murine and human skin tumorigenesis. This is functionally important, since activin promoted skin tumorigenesis in mice induced by the human papillomavirus 8 oncogenes. This was accompanied by depletion of epidermal γδ T cells and accumulation of regulatory T cells. Most importantly, activin increased the number of skin macrophages via attraction of blood monocytes, which was prevented by depletion of CCR2‐positive monocytes. Gene expression profiling of macrophages from pre‐tumorigenic skin and bioinformatics analysis demonstrated that activin induces a gene expression pattern in skin macrophages that resembles the phenotype of tumor‐associated macrophages in different malignancies, thereby promoting angiogenesis, cell migration and proteolysis. The functional relevance of this finding was demonstrated by antibody‐mediated depletion of macrophages, which strongly suppressed activin‐induced skin tumor formation. These results demonstrate that activin induces skin carcinogenesis via attraction and reprogramming of macrophages and identify novel activin targets involved in tumor formation. Synopsis: The growth and differentiation factor activin promotes skin tumorigenesis by recruiting macrophages and promoting their differentiation to a pro‐tumorigenic phenotype. Activin overexpression is an early event in murine and human skin tumorigenesis. Activin strongly promotes skin tumorigenesis in mice induced by the human papillomavirus 8 oncogenes. Activin‐induced skin tumorigenesis is associated with a strong increase in macrophage infiltration and their reprogramming to a phenotype resembling tumor‐associated macrophages. Antibody‐mediated depletion of macrophages suppressed activin‐induced skin tumor formation through inhibition of tumor cell proliferation and angiogenesis. Abstract : The growth and differentiation factor activin promotes skin tumorigenesis by recruiting macrophages and promoting their differentiation to a pro‐tumorigenic phenotype.